Production Costs And Determining The Optimum Size For Producing Sugar Beet In Al-Ghab (Journal of Hama University, 2021)
The Sugar beet crop in Syria is an important strategic crop due to the success of its cultivation in most regions of the country, in addition to its contribution to filling part of the needs of the local market of sugar, and providing it for many job opportunities. So this research aims to estimate the structure of production costs of sugar beet in 2018 season, based on a questionnaire for a random sample that included 170 farmers in the Al-Ghab area. The results showed that the average total costs of producing sugar beets for the 2018 season amounted to approximately 137 thousand SP/dunum. Labor costs accounted for 28.8% of total costs, while costs of production requirements accounted for 51.5%. Also appreciated the cost function of the sugar beet crop in the short and long term, and compared the optimum size for two terms, it reached 6.14 tons/dunum in the short term, and 8.2 tons/dunum in the long run. In addition to estimating the most profitable production volume it reached 7.28 tons/dunum in the short term, while the optimum farm capacity reached 13.1 dunums.